Penatalaksanaan Fisioterapi Pada Kasus Pneumothoraks Dextra Di RSU PKU Muhammadiyah Yogyakarta - Pratama, Vindo Dwika, Isnaini Herawati S.Fis.,S.Pd,.M.Sc (2015)
Background: Pneumothorax dextra is a respiratory disorder with symptoms of asphyxia, reduced thorax expansion and functional activity disturbances. The disorder can be overcome by using exercise therapy such as Breathing Exercise, Thoracic Exercise, Cuping, and ambulation transfer. The exercise therapy is modality used to relieve asphyxia and to increase thoracic expansion. Purpose: Purpose of the research is to know effect of exercise therapy on pneumothorax dextra case by mitigating asphyxia and increasing thoracic expansion. Method: The research uses quasi-experimental method with one group pre-andposttest design. Functional ability is measured by using Disability Index. Results of Analysis: Results of statistical test indicated better condition after administration of therapy with exercise therapy modality of Breathing exercise, Thoracic expansion exercise, Cuping, and Ambulation Transfer. Conclusion: Function ability of pneumothorax dextra patient can be improved by using exercise therapy such as Breathing Exercise, Thoracic Exercise, Thoracic Expansion exercise, Cuping, and Ambulation Transfer.